A ergonomia na atividade leiteira: avaliação das condições de trabalho dos ordenhadores na região de Campo Mourão - PR - Oliveira, Claudilaine Caldas de (2011)
This study aimed to evaluate the posture of workers in relation to the activities of milking management and milking handling of the milk cattle associating them to production systems applied by milkers the Region of Campo Mourão Cities Community (COMCAM). As a methodology, aiming to identify the presence of musculoskeletal symptoms, the study was divided in two stages: the first was to identify the demographic profile of the sample (163 milkers) through a questionnaire and then it was tried to obtain information about problems related to pain and or discomfort by applying the standard Nordic questionnaire (QNP). In the second stage, it was performed the Analysis of the Activity on six farms (nine milkers) to identify risk factors of ergonomic nature. For registration and evaluation of positions, it was used the method Rapid Entire Body Assessment (REBA) and regarding the evaluation of loads, it was used the equation of the National Institute for Occupational Safety and Health (NIOSH). It was identified a total of 87% of workers complaining of pain or musculoskeletal discomfort and such symptoms were presented in most cases with multifocal aspect, that is 86 workers (60.56%) indicated the presence of pain in different body segments at the same time. The highest prevalence of pain in the last 12 months was in the lumbar region (73.94%), regarding chronic aspects, in the last seven days days the most affected region was the hips (64.29%) and regarding severity, the most severe pain conditions involved of the region of the lower limbs (legs with 37.93%) causing removal from the work activities. Regarding production systems, it was first compared the hand milking systems to mechanical one in relation to all types of pain and it was found that the hand milking was more harmful (95.31% of pain), however, from the five studied production systems, the milking pail with the foot in the parlor (gap), proved to be more damaging (100% pain). Following the milking activity, it was possible to identified that the mainadopted postures during the working shift are the tilt, trunk bending and cargo handling between 12 to 60 kg and from this, it can characterizes the milker activity as a job that requires, in most tasks, constrained postures, with great effort level, fact itself that may contribute to the development of musculoskeletal injuries in these workers. Thus, ergonomic recommendations were proposed in order to reduce these constraining postures of milkers and consequently to improve the quality of life on the workplace.